Oil extraction from spent coffee ground (SCG) using hydrous ethanol at different extraction time / Nur Athirah Abdul Khalid - Abdul Khalid, Nur Athirah (2023)
Coffee is a well-known beverage all around the world. It was because coffee included caffeine, which can give you the energy you need to sleep. The coffee beans are being processed, and nearly half of them will end up as wasted coffee grounds (SCG). Every year, approximately 9 million tonnes of SCGs are created worldwide, and they are inappropriately disposed of. It has become one of the issues leading to global pollution. As a result, an experiment was carried out to extract oil from SCGs using hydrous ethanol as a solvent and hand extraction at varied extraction intervals of 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, and 80 minutes. Throughout the trial, the maximum percentage yield was recorded at 60 minutes with 5.34% of coffee oil.